Controlled nanostructures and simultaneous passivation of black phosphorus (phosphorene) with Nafion. Issue 2 (28th January 2020) - Kumar, Avneesh
Abstract: Abstract : Structural evolution induced and driven by a dual system and simultaneous passivation of phosphorene are reported. Different nano-objects of phosphorene or black phosphorus (BP) are obtained using a new method of exfoliation, in which solvent and an ionic polymer are combined to weaken the van der Waals forces and to scissor the nanosheets. Nanoribbons, nanorods, and nanoneedles are obtained under mechanical force and ambient conditions. Ionic polymer chains assist in curling the monolayer or few-layer nanosheet. Nafion is chosen to exfoliate the bulk BP and induce a morphological transition in BP nanosheets. The exfoliation of BP nanosheets results into thin and specific structures such as nanosheets/rods/needles. The nanosheets of phosphorene are covered and passivated simultaneously by the polymeric sheath that protects the nanosheets from degradation or oxidation and can be integrated with a device directly without any further coating.